Wireless crack detection and analysis system for nuclear power plant. Issue 1 (2nd January 2016) - Lee, Sangdong; Bian, Ying-Hua; Lim, Sang Boem
Abstract: After the Fukushima nuclear accident, attention has been paid toward the construction and maintenance of nuclear power plants. A nuclear material spill originating from cracks in the nuclear plant's concrete structure due to natural disasters such as earthquakes or inappropriate planning and construction will have harmful consequences. There are ongoing studies for developing technologies to predict cracking in a structure when said structure is harmed by unexpected damages. This paper deals with studies on a ubiquitous crack detection and analysis system that is a combination of the extended finite element method (X-FEM) and ubiquitous sensor network (USN) technologies and can respond quickly when a nuclear plant is damaged. Because X-FEM is a considerably developed analysis technology, its use allows for relatively accurate crack analysis. Thus, the combined ability of real-time damage reporting using USN and data-based estimation of the scale of damage through crack analysis is expected to be useful for reducing damages due to unpredicted calamities.